STRATEGI DAN TANTANGAN BAZNAS DALAM PENGELOLAAN DANA ZAKAT PRODUKTIF TERHADAP PENGENTASAN KEMISKINAN DI TANGERANG SELATAN - Pangestu, Figo Aji; Bachroyani, M Adib; Kharazi, Fayyad; Nafi'i, Muhammad Abrar (FADZAT: Jurnal Ekonomi Syariah, 2024)
This research aims to analyze the strategies and challenges in managing productive zakat conducted by the National Zakat Agency (BAZNAS) of South Tangerang City in efforts to alleviate poverty. This research employs a qualitative approach with descriptive analysis, where data collection was carried out through in-depth interviews, field observations, and literature reviews from primary and secondary sources. The findings reveal that economic, educational, health, and disaster empowerment programs implemented by BAZNAS have significantly contributed to improving the welfare of some mustahik (zakat recipients). However, major challenges such as the lack of entrepreneurial spirit among mustahik, limited zakat funds, and insufficient focus on sustainable empowerment remain as obstacles. Therefore, the proposed strategies include providing business capital, entrepreneurship training, and long-term mentoring to ensure that productive zakat can deliver positive, optimal, and sustainable impacts in poverty alleviation efforts within the region.